A chemical representation of a chaotic system with a unique stable equilibrium point. Issue 13 (2018) - Méndez-González, J.M.; Quezada-Téllez, Luis A.; Fernández-Anaya, Guillermo; Femat, R.
Abstract: In this paper we present a chemical representation of a chaotic system with only one stable equilibrium point. The approach invokes cooperative catalysis and slow-fast reactions, primarily. The obtained chemical based chaotic dynamical system preserves the eigenvalues of the unique and stable equilibrium point along with the Lyapunov's dimension and exponents of the original one.